Disseminated Herpes Zoster in the Immunocompetent, A Case at Zinder National Hospital - Doutchi, Mahamadou; Abdoul-aziz, Garba; Kadidia, Kassoumou; Lamine, Moustapha M.; Laouali, Harouna M.; Ibrahim, Alkassoum; Adehossi, Eric; Danmata, Salissou (European Scientific Journal, ESJ, 2019)
Introduction: Herpes zoster, shingles, is a secondary pathology due to a reactivation of the varicella-zoster virus (VZV) and common in the general population. It is responsible for a painful skin rash localized in the area of the body innervated by a nerve root. The rash can be widespread affecting several dermatomes especially in the immunocompromised subject. Observation: We report an observation of disseminated shingles in an immunocompetent adult hospitalized in the Internal Medicine Department of Zinder National Hospital. AT 55 years old, was admitted for management of a very painful skin rash. Pruriginous vesicles extended diffusely out of the metameric topography to all the enveloping membranes of the body including vulvo-vaginal and oral enanthem. Biologically, blood count (CBC), blood glucose, and renal function were normal. Human immunodeficiency virus (HIV) status was negative. The clinical course was uneventful characterized by apyrexia at 48 hours and drying of the lesions. Medical care was based on symptomatic treatment. Conclusion: Shingles is a common viral disease, but potentially serious in some situations. The disseminated form is exceptional in the immunocompetent subject. Its detection and early treatment ensure a reduction in the severity of the complications.